Body mass index profile in adolescents and its relation with weight concerns - Pereira, Filomena (2017)
The percentage of obese adolescents has increased during the past years, which as lead the World Health Organization to consider obesity as the main epidemic of the XXI century. However, adolescents are not immune to body image and weight concerns. This sensibility regarding weight might be an asset, allowing a healthy eating behaviour. Objectives: Analyse the adolescent’s body mass index (BMI); Evaluate the relation between the BMI and the weight concerns. Methods: Restrictive, quantitative and transversal study. By gathering a simple random sample, and considering a sampling error of 3.5%, a sample of 600 adolescents (44% of the male sex and 56% of the female sex) with ages among 12-18 years old and attending the EB 2/3 Schools, High Schools and Professional Schools from Bragança, was studied. The BMI was determined through the calculation of the ration between the measure of the body mass in kilograms and the height in meters, squared (mass (kg)/height (m)2), and classified with the criteria established by the Centers for Disease Control and Prevention. For the collection of data regarding weight concerns, it was used a self-administered questionnaire adapted from Luciana Apetito et al (2010). For the statistics analysis, it was used the SPSS programme version 14.0 (2005) for Windows, Microsoft. Results: 7,2% of boys and 5,7% of girls, in the age group 12-14 years old, and 15,9% and 10,1%, respectively, in the age group of 15-18 years old, had overweight/obesity. At a 5% significance level, it was demonstrated that the BMI was statistically dependent of the sex (ET: 5.171; vp: 0,160) and the age group (ET: 1,900; vp: 0,593). Also, 61,2% of boys and 83,6% of girls stated that they worry about their weight. The concerns regards weight are statistically associated to the BMI observed (ET:17,225; vp: 0,001) Conclusion: The results showed that 23,1% of boys and 15,8% of girls have a BMI above the recommended amounts and, also, that it is statistically dependent of weight concerns. From this point of view, the interventions among young people must be multifaceted, never forgetting the elements that constitute the human being (psychological and biological).